Ipomoea aculeata Blume (Convolvulaceae) – A New Record for Maharashtra, India - Borude, D.B.; Salunke, N.L.; Mengal, S.G.; Deokar, V.D.; Kattee, A.V.; Shimpale, V.B.; Chandore, A.N. (Journal of the Bombay Natural History Society (JBNHS), 2025)
No Abstract.